TRANSFER INFORMASI INTRA INDUSTRI ATAS PENGUMUMAN RIGHTS ISSUE DI BURSA EFEK JAKARTA - Hana Norhamida (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
The objective of this study is to examine the existence of intra-industry information transfer of the announcement of rights issue. This research has three tests. First, it is the information content test of the announcement of rights issue by issuers firm (event study standard). Second, it is an intra-industry information transfer test that examines information content of the announcement of rights issue by non-issuers firm. Two-first tests verify the significance of abnormal return obtained by issuers firm and non-issuers firm through t-test. Third, it is a regression test, which is to examine the influence of variable of bid-ask spread and variable of relative size of rights issue – as independent variables to variable of non-issuers firm’s abnormal return – as dependent variable. The samples of this study consist of 32 issuers firm and 149 non-issuers firm. All of them are the members of manufacturing firm listed in Jakarta Stock Exchange (JSX) in the period of 1997-2002. This study uses purposive sampling method. The window period is ten days surrounding of the announcement of rights issue (-5, 0, +5). The event date is the listing date of rights issue in JSX.The results of this study are as follows. First, there is information content for the announcement of rights issue that is shown with the existence of marginally significant negative abnormal return obtained by issuers on t-1. This result confirms Marsden (2000). Second, there is an evidence about intra-industry information transfer – there is a significantly positive abnormal return on t-3 and a significantly negative abnormal retun on t+4. Both of them show the existence of contagion effect because the direction of issuers firms and non-issuers firm’s abnormal return on t-3 and t+4 (when the intra-industry information transfer exists significantly) is equal. It shows that commonality industrial factors have the role in this research. The negative intra-indutry information transfer confirms Szewczyk (1992). Third, there is not a significantly influence for variable of bid-ask spread and variable of relative size of rights issue to variable of non-issuers firm’s abnormal return.